Biofiltration using C. fluminea for E.coli removal from water: Comparison with ozonation and photocatalytic oxidation. (October 2018) - Gomes, João F.; Lopes, Ana; Gonçalves, Daniel; Luxo, Cristina; Gmurek, Marta; Costa, Raquel; Quinta-Ferreira, Rosa M.; Martins, Rui C.; Matos, Ana
Abstract: Corbicula fluminea, an Asian clam, is one of the worst invasive species in Europe that can survive in very adverse environmental conditions. Despite its negative impacts, the species also has the capacity to bioaccumulate heavy metals, contaminants and can be exploited for wastewater treatment purposes. The capacity of the Asian clam to remove Escherichia coli, used as fecal contamination indicator, was analyzed. Conventional wastewater treatment plants are not suitable to remove bacteria, thus resulting in treated municipal wastewater with high bacterial loads. E. coli clearance rate was analyzed as function of the number of clams. The bivalves can remove bacteria until concentrations below the detection limit in about 6 h. The adsorption on the clam shells' and bioaccumulation on the soft tissues were also analyzed. The depuration of clams along 48 h were analyzed revealing that no bacteria was detected in the water. Thus, these results suggest that Asian clam can bioprocess E. coli . On the other hand, results obtained by this methodology were compared with ozonation and photocatalytic oxidation using TiO2, Ag, Au, Pd-TiO2 . In all treatments it was possible to achieve concentrations of E. coli below the detection limit. However, photocatalytic oxidation demands about 4700 folds more energy than ozonation, besides the costs associated with catalysts. Comparing complexity of ozonation with biofiltration, this study suggests that application of biofiltration using C. fluminea can be a suitable solution to minimize the presence of bacteria in wastewater, reducing environmental and economic impacts. Highlights: Asian clams can be a suitable solution to remove E. coli from water. Use of invasive bivalves for water disinfection could be a management alternative. Pd and Ag metals doped on TiO2 (Pd, Ag) promote the E. coli disinfection. Biofiltration, ozone and photocatalysis were efficient processes to wastewater disinfection.